2020
DOI: 10.1021/acs.jctc.0c00615
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Free-Energy Calculations of Metalloenzymes in Drug Discovery via Implementation of LFMM Potentials

Abstract: To address some of the inherent challenges in modeling metalloenzymes, we here report an extension to the functional form of the OPLS3e force field to include terms adopted from the ligand field molecular mechanics (LFMM) model, including the angular overlap and Morse potential terms. The integration of these terms with OPLS3e, herein referred to as OPLS3e+M, improves the description of metal–ligand interactions and provides accurate relative binding energies and geometric preferences of transition-metal compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
(122 reference statements)
0
9
0
Order By: Relevance
“…However, the number of possible RNA targets far exceeds that of druggable protein targets. Multiple studies have shown that RNA is a suitable small-molecule drug target. However, FEP prediction targeting RNA faces several major challenges including the limited accuracy of RNA and related metal-ion FFs, the issue of proper sampling of flexible RNA structures, and the complications arising in a highly charged simulation environment as that of RNA and counterions. Addressing these issues would open up an entirely new avenue of FEP applications for drug discovery and is expected to be a subject of interest for the whole FEP research community in the near future. How to interpret FEP prediction results: From retrospective validation of FEP predictions, we know that it is unavoidable to have false negative and false positive results in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of possible RNA targets far exceeds that of druggable protein targets. Multiple studies have shown that RNA is a suitable small-molecule drug target. However, FEP prediction targeting RNA faces several major challenges including the limited accuracy of RNA and related metal-ion FFs, the issue of proper sampling of flexible RNA structures, and the complications arising in a highly charged simulation environment as that of RNA and counterions. Addressing these issues would open up an entirely new avenue of FEP applications for drug discovery and is expected to be a subject of interest for the whole FEP research community in the near future. How to interpret FEP prediction results: From retrospective validation of FEP predictions, we know that it is unavoidable to have false negative and false positive results in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the application of FEP to predict changes in binding affinity proximate to bound transition metals remains one of the more challenging problems in force field modeling. Improvements to the force field targeting this context are under active development in this group, but significant development remains before a streamlined and robust solution is available. The present ion vdW work also makes clear the limitations of pairwise additive potentials.…”
Section: Discussionmentioning
confidence: 99%
“…This success has motivated new developments aimed at extending the reach of these free energy methods to cover more ambitious problems in structure-based molecular design, including proper handling of buried water molecules, variable tautomer and ionization states, covalently bound ligands, , and transition metal coordination . These advances can introduce greater sensitivity to chemical space regimes that present outstanding challenges to the fidelity of the model.…”
Section: Introductionmentioning
confidence: 99%
“…Using LFMM, Paesani and co-workers performed molecular dynamics and Monte Carlo simulations to observe changes in the spin-crossover transition of a Fe­(II) SCO MOF in the presence of additional water molecules in the unit cell that alter the ligand field environment around the Fe­(II) metal (Figure ). Other recent extensions of LFMM have been developed for metalloenzyme modeling …”
Section: Molecular Modeling For Transition-metal Chemistrymentioning
confidence: 99%